GOOD CORPORATE GOVERNANCE (GCG) DAN PEMAHAMANNYA DI DUNIA BISNIS - Raharjo, Teguh Budi (PERMANA, 2010)
GCG contains among other benefits can reduce the agency cost, the cost to be borne by the shareholders from delegating authority to the management; lower cost of capital as a result of the company managed in a healthy and responsible, increase the value of company stock, and create support for stakeholders on the company Keywords : Good Corporate Govenance, agency cost